A gain-of-function mutation in the CLCN2 chloride channel gene causes primary aldosteronism - Fernandes-Rosa, Fabio L.; Daniil, Georgios; Orozco, Ian J.; Göppner, Corinna; El Zein, Rami; Jain, Vandana; Boulkroun, Sheerazed; Jeunemaitre, Xavier; Amar, Laurence; Lefebvre, Hervé; Schwarzmayr, Thomas; Strom, Tim M.; et al. (Nature genetics, 2018)
Primary aldosteronism is the most common and curable form of secondary arterial hypertension. We performed whole-exome sequencing in patients with early-onset primary aldosteronism and identified a de novo heterozygous c.71G>A/p.Gly24Asp mutation in the CLCN2 gene, encoding the voltage-gated ClC-2 chloride channel 1 , in a patient diagnosed at 9 years of age. Patch-clamp analysis of glomerulosa cells of mouse adrenal gland slices showed hyperpolarization-activated Cl – currents that were abolished in Clcn2 −/− mice. The p.Gly24Asp variant, located in a well-conserved ‘inactivation domain’ 2 , 3 , abolished the voltage- and time-dependent gating of ClC-2 and strongly increased Cl – conductance at resting potentials. Expression of ClC-2 Asp24 in adrenocortical cells increased expression of aldosterone synthase and aldosterone production. Our data indicate that CLCN2 mutations cause primary aldosteronism. They highlight the important role of chloride in aldosterone biosynthesis and identify ClC-2 as the foremost chloride conductor of resting glomerulosa cells. A gain-of-function mutation in the CLCN2 chloride channel gene (encoding ClC-2) causes primary aldosteronism. The mutation abolishes voltage-dependent gating of ClC-2, highlighting a role for chloride conduction in regulating aldosterone biosynthesis.